Enhancing Crime Control Partnerships Across Government: Examining the Role of Trust and Social Capital on American and Australian Waterfronts. (December 2013) - Brewer, Russell
This article discusses the importance of trust in furthering crime control partnerships among government agencies. Drawing upon fieldwork undertaken on American and Australian waterfronts, evidence is presented showing that trust played an integral role in shaping interagency partnerships at both sites. In abundance, trust was shown to help build social capital and promote harmonious relationships, whereas when lacking, collaborative activity was stunted. This article examines the successes and failures of partnerships in each case study, and concludes by identifying a range of factors that have been shown to promote trust, build social capital, and enable interagency partnerships to flourish.